1993
DOI: 10.1016/s0022-5347(17)35413-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Her-2/Neu may be an Indicator of Poor Prognosis in Prostate Cancer

Abstract: Previous reports have shown that Her-2/neu oncogene expression in human breast cancer and ovarian cancer may be associated with poorer prognosis. We report the expression of Her-2/neu on fresh samples of known prostatic adenocarcinoma but not on those of benign prostatic hypertrophy. Using a monoclonal antibody (TA1) directed against human Her-2/neu oncogene product and an immunohistochemical staining method, no Her-2/neu expression was noted with benign prostatic hypertrophy (15 samples). With prostatic adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 11 publications
2
49
1
Order By: Relevance
“…27 Sadasivan et al found that 9 of 25 prostate carcinoma samples (36%) showed HER-2/neu overexpression, and such overexpression was correlated with tumor grade, stage, and high S-phase and DNA aneuploidy. 15 However, other investigators have reported contradictory results. Formalin fixed prehormone treatment and posthormone treatment specimens from 47 patients were negative for HER-2/neu overexpression when they were evaluated by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…27 Sadasivan et al found that 9 of 25 prostate carcinoma samples (36%) showed HER-2/neu overexpression, and such overexpression was correlated with tumor grade, stage, and high S-phase and DNA aneuploidy. 15 However, other investigators have reported contradictory results. Formalin fixed prehormone treatment and posthormone treatment specimens from 47 patients were negative for HER-2/neu overexpression when they were evaluated by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…An overexpression of c-ras, c-myc and c-sis oncogenes has been reported (Fleming et al, 1986;Viola et al, 1986;Buttyan et al, 1987), but ras mutations are rare (Gumerlock et al, 1991;Moul et al, 1992). A role of HER-2/neu is not certain (Kuhn et al, 1993;Sadasivan et al, 1993). Recent evidence suggests that tumoursuppressor genes (TSGs) might be more important for the development of prostate carcinoma (Bookstein, 1994;Isaacs, 1995).…”
mentioning
confidence: 99%
“…60 High C-ERB-B2 expression is associated with anti-androgen therapy and may contribute to androgen-independence in PC. 61 Sadasivan et al 62 found that C-ERB-B2 expression correlated with advanced stages and higher Gleason scores. Conversely Kuhn et al 63 in a preliminary study of 53 radical prostatectomy (RP) cases, found that C-ERB-B2 protein expression did not predict serological or clinical recurrence.…”
Section: The C-myc Oncogenementioning
confidence: 99%